EVALUASI RISK MATURITY DALAM PENGELOLAAN KEUANGAN PUBLIK - Dwiyanto, Muhaswad; Supriadi, Yudi Nur; Nurdiani, Elia Erna (Gapenas Publisher, 2025)
Risk management is a strategic instrument in public sector governance that plays an important role in supporting accountable and sustainable public financial management. This study aims to analyze the level of maturity of the implementation of risk management and its influence on public financial management at the Directorate General of Culture (now the Ministry of Culture of the Republic of Indonesia). The research approach uses an explanatory quantitative method with survey techniques, where data is collected from employees involved in financial management, program planning, and risk management. Data analysis was carried out using Structural Equation Modeling Partial Least Squares (SEM-PLS). The results of the study show that the implementation of risk management at the Directorate General of Culture is in the risk defined category, which indicates that risk management policies and guidelines have been available and communicated, but the implementation has not been fully integrated evenly across all work units. The risk register is still partially prepared, so risk management practices tend to be administrative and not optimal as a basis for strategic decision-making. Nevertheless, the results of empirical analysis show that the level of risk maturity has a positive and significant effect on public financial management, especially in strengthening financial accountability, the effectiveness of internal controls, and performance-based budget management. This research confirms that increasing risk maturity is an important prerequisite in strengthening public sector financial governance and management. These findings provide policy implications for the need to integrate risk management into the planning, budgeting, and performance evaluation cycles, strengthen the capacity of human resources, and utilize technology-based information systems to support more effective and sustainable risk management.